Peran Karakteristik Individu sebagai Moderator dan Pemasaran Relasional sebagai Mediator Pengaruh Kepuasan terhadap Loyalitas (Studi pada Nasabah Bank Syariah di Jawa Timur) - Mokhamad Arwani; Djumilah Zain; Surachman -; Djumahir - (Jurnal Aplikasi Manajemen, 2012)
The main focus of this research is to reveal and interpret the mediation role of the relationship marketing between satisfaction and loyalty, as well as to test the moderator role of individual characteristics in relation with the influence of satisfaction on loyalty. The samples determinan in this study was accidental sampling. Of 160 questionnaires, the returned ones were 112. This number of samples has been eligible for conducting SEM technique analysis. The analysis showed that customers who are satisfied will be loyal to Islamic banks if the customer have adequate educational background and knowledge about Islamic banking. The satisfied customers will enhance long-term relationship with the Islamic banks in form of mutual trust, good communication, and trust that the bank will provide good services. The satisfied customers will enhance the mutual trust and good communication, which eventually create customers loyalty.Keywords: satisfaction, individual characteristics, relationship marketing, loyalty, Islamic bank